2012
DOI: 10.1177/0897190012451910
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Diazepam and Nordiazepam in 1000 Blood Samples From Apprehended Drivers—Therapeutic Use or Abuse of Anxiolytics?

Abstract: Using an in-house forensic toxicology database, we selected 1000 cases of driving under the influence of drugs (DUIDs) over a 12-month period if diazepam (D) and nordiazepam (ND) were both present in the blood samples. Quantitative analysis of D and ND in blood was done by solvent extraction (butyl acetate) and capillary column gas chromatography (GC) with a nitrogen-phosphorous (N-P) detector. The limits of quantitation of this analytical method for D and ND in blood were 0.05 mg/L. The correlation between D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…However, an on-going study found that only 26% of drivers with diazepam in blood had a prescription issued to them for this medication, so 84% of drivers had obtained the drug illegally (Tjäderborn, personal communication). According to the present study, the median concentration of diazepam in blood of fatally injured drivers was 0.10 mg/L, which is sub-therapeutic and much lower than the median concentration of 0.2 mg/L in apprehended drivers not involved in fatal crashes [28].…”
Section: Discussionmentioning
confidence: 96%
“…However, an on-going study found that only 26% of drivers with diazepam in blood had a prescription issued to them for this medication, so 84% of drivers had obtained the drug illegally (Tjäderborn, personal communication). According to the present study, the median concentration of diazepam in blood of fatally injured drivers was 0.10 mg/L, which is sub-therapeutic and much lower than the median concentration of 0.2 mg/L in apprehended drivers not involved in fatal crashes [28].…”
Section: Discussionmentioning
confidence: 96%
“…The results indicated that lower detection limits were achieved by TD-ESI/MS/MS than those of TD-ESI/MS for the detection of adulterant standards prepared in methanol and of those spiked in different herbal preparations (Table ). Human serum >20 μg/mL acetaminophen, >15 μg/mL caffeine, > 1.5 μg/mL diazepam, > 20 μg/mL phenytoin, and >45 μg/mL phenylbutazone . Such overdose levels encountered in actual clinical practice are far higher than the LODs of TD-ESI/MS described in this study.…”
Section: Resultsmentioning
confidence: 54%
“…Certainly, therapeutic concentrations of diazepam may be exceeded in blood of the persons abusing it. To our knowledge, the maximum concentration of diazepam was observed in humans to be as high a 7.6 mg/L corresponding to 26.7 μM [ 43 ]. Therefore, although at standard therapeutic dosages diazepam would not affect immune cells in humans, at higher doses found in plasma of substance abusers immunological effects might take place.…”
Section: Discussionmentioning
confidence: 99%